Game Gatotkaca Adventure On Java’s Island - Deni Rinaldi; Muchammad Naseer; Nova Agustina (International Journal of Computer, Network Security and Information System, 2019)
Abstract— Indonesia has a variety of cultures and traditional arts spread from Sabang to Merauke with the uniqueness and characteristics of each culture itself. Wayang is one of the most prominent peaks of Indonesian culture and art among many other cultural works. Gatotkaca is an adaptation of Indian literature, namely Ramayana and Mahabarata. Game is one of the media that can be used in conveying a goal. The objectives contained in the game have various types of education, entertainment and simulation. At this time the game is growing and there are also many applications and libraries that are used to develop games. For example Construct 2, Game Maker: Studio, Unity, Godot Game Engine, Unreal Engine 4 and others. With this application, the authors hope this application becomes an interactive and interesting learning media so that it can help provide education, and preserve Indonesian culture, especially in Indonesian wayang.